Optimization of EDM parameters for micro/meso fabrication - Ali, Mohammad Yeakub; Ammar, S. M.; Baayah, N.; Aishah, S.; Zaliha, S.; Hayati, N. (2006)
This paper discusses the possibility of micro/meso fabrication using conventional electrodischarged machining (EDM). Design of experiment (DOE) technique is used to optimize the process and to determine how the input parameters affect the fabrication in micro/meso scale. The selected input parameters are peak current, on-time and off-time. The responses are surface roughness and accuracy. The test micro/meso features were channels on stainless steel. The surface of the microchannels was inspected by using scanning electron microscope (SEM). The surface finish and accuracy were measured by Mitutoyo surface roughness tester and profile projector PJ-311 respectively. The data used in fabrication and obtained from the measurement were analyzed using DOE software. The results showed how the parameters greatly influence the surface quality and accuracy of the fabricated channel. It was observed that the combination of factor values of 2.1A peak current, 5 μs on-time and 10 μs off-time yields the optimum surface roughness 2.5 μm Ra and accuracy ±3%. The fabricated microchannles were further used in replication of polymer micro/meso components by hot embossing.